2003
DOI: 10.1046/j.1439-0434.2003.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Grasses Phalaris arundinacea, Miscanthus sinensis and Echinochloa crus‐galli, and Barley and Cereal Yellow Dwarf Viruses

Abstract: The grass species Miscanthus sinensis, Echinochloa crus‐galli and Phalaris arundinacea may be useful biomass crops. In glasshouse inoculations with two isolates of Barley yellow dwarf virus (BYDV)‐MAV and BYDV‐PAV and one of Cereal yellow dwarf virus (CYVD)‐RPV, E. crus galli was infected by all three virus isolates, P. arundinacea by BYDV‐MAV and CYDV‐RPV, but M. sinensis only by BYDV‐MAV. All three hosts became very difficult to infect after several weeks’ growth. Symptoms were inconspicuous; dry matter yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Despite studies finding some incidence of agricultural disease in Miscanthus (Christian et al, 1994;O'Neill & Farr, 1996;Ahonsi et al, 2010), it does not appear to have become a significant problem after more than a decade of commercial growing in the UK, and pesticides are still not generally considered necessary. Lamptey et al (2003) found that while Miscanthus (M. sinensis in this case) was susceptible to yield losses from infection with Cereal Yellow Dwarf Virus after being inoculated with them in laboratory experiments, it was more resistant than other energy grasses in their study. All were difficult to infect once the plants had got past the seedling stage but of 18 Miscanthus plants none were found to become infected when exposed to the virus after stem extension.…”
Section: Pesticidementioning
confidence: 74%
See 2 more Smart Citations
“…Despite studies finding some incidence of agricultural disease in Miscanthus (Christian et al, 1994;O'Neill & Farr, 1996;Ahonsi et al, 2010), it does not appear to have become a significant problem after more than a decade of commercial growing in the UK, and pesticides are still not generally considered necessary. Lamptey et al (2003) found that while Miscanthus (M. sinensis in this case) was susceptible to yield losses from infection with Cereal Yellow Dwarf Virus after being inoculated with them in laboratory experiments, it was more resistant than other energy grasses in their study. All were difficult to infect once the plants had got past the seedling stage but of 18 Miscanthus plants none were found to become infected when exposed to the virus after stem extension.…”
Section: Pesticidementioning
confidence: 74%
“…Lamptey et al . () found that while Miscanthus ( M. sinensis in this case) was susceptible to yield losses from infection with Cereal Yellow Dwarf Virus after being inoculated with them in laboratory experiments, it was more resistant than other energy grasses in their study. All were difficult to infect once the plants had got past the seedling stage but of 18 Miscanthus plants none were found to become infected when exposed to the virus after stem extension.…”
Section: Chemical Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanky (1991) reported diverse fungi species from the Ustilaginales family on German populations of RCG plants. After experimental inoculations in glasshouse, Lamptey et al (2003) showed that growth of adult and seedlings of RCG can be severely suppressed (up to 45%) by the Barley yellow dwarf virus (a widespread disease in Europe) and by Cereal yellow dwarf virus, as well as their natural vectors (aphid species). The Wheat dwarf virus and its insect vector were also shown to infest RCG plants in natural conditions (Mehner et al, 2003).…”
Section: The Unknown Influence Of Herbivores and Pathogensmentioning
confidence: 99%
“…Overall, these studies indicated that similar to row crops, fungal pathogens pose a serious threat to these bioenergy crops. In addition, viruses also pose a threat to bioenergy feedstocks, which have been documented in switchgrass and miscanthus (Chatani et al, 1991; Turina et al, 1998; Lamptey et al, 2003). …”
Section: Role Of Lignin In Plant Defensementioning
confidence: 99%